Implementasi Strategi Pembelajaran Student Teams Achivement Division (STAD) pada Mata Pelajaran Pendidikan Agama Islam di SMP Swasta Madani Marindal-1 - Arlina Arlina; M. Nuha Hidayat; Meida Sari Siregar; Yola Anjellia Swanto (Tarbiatuna: Journal of Islamic Education Studies, 2024)
This research aims to improve student learning outcomes by applying the Student Teams Achivement Division (STAD) learning strategy to class VIII students at Madani Marindal-1 Private Middle School. This research uses qualitative methods with a phenomenological approach. The data collection methods used were interviews, observation, documentation and group discussions. Class VIII students were participants in this research. The data analysis method in this research was carried out from pre-field implementation to completion in the field. Data validation was carried out using source triangulation. The data analysis used uses Huberman's opinion, namely data reduction activities or making reports from start to finish which selects basic data found in the field, presents the data, examines incomplete data, and finally draws conclusions. From the results of observations and interviews conducted by the author, it is known that the application of the Student Teams Achievement Division (STAD) learning strategy increases students' learning motivation.